Fostering sustainable development in the age of technologies - Sharma, Rohit; Shishodia, Anjali; Gupta, Ashish (Bingley, U.K. : Emerald Publishing Limited, 2023)
The world is changing at an unprecedented pace and organizations worldwide are finding it difficult to match their operational efficiency and sustainable development targets with the United Nations Sustainable Development Goals (UNSDGs). Due to massive scarcity of resources, global supply chains are under immense pressure, leading to social, economic, and environmental challenges. Holistic sustainable development across social, economic, and environmental dimensions to create an equitable society varies widely in its efficiency towards creating a resilient and inclusive future. Fostering Sustainable Development in the Age of Technologies highlights the interplay between various disruptive technologies such as Artificial Intelligence, Autonomous robots, Big Data Analytics, Blockchain, Cloud Computing, and Digital Twins, and holistic sustainable development. In the highly dynamic business environment, there is an urgent need to catch up with the paradigm shift being created using these technologies. The studies brought together here emphasise how various disruptive technologies can aid in sustainable development, offering possible strategies to help tackle the challenges we face today and embrace the new normal. Collaboration, adaptation, and continuous learning hold the key in overcoming the grand societal challenges and maintaining a balance between social, economic, and environmental dimensions. This edited collection appeals to a wide range of academics and professionals including graduate, postgraduate, and PhD research scholars, and faculty members in the areas of International Management, International Business, International Marketing, Finance, Human Resources and Corporate Governance. They are also of interest to Government Agencies, Practicing Managers, Research Agencies, and Libraries of Business Management Colleges and Universities.
Chapter 1. The role of digital technology in achieving sustainable development goals (sdgs): A systematic literature review, bibliometric analysis, and content analysis / Arushi Bathla, Priyanka Aggarwal, and Kumar Manaswi -- Chapter 2. Digital technologies, sustainable development goals and the grand societal challenges in the context of slum dwellers of kolkata, India / Atiba Batul, K. D. Ghosh, and S. Palit -- Chapter 3. Applications of disruptive technologies in professional services / Chandan Jha and Amit Sachan -- Chapter 4. Confrontation strategy for evolution of future employment / Donghun Yoon -- Chapter 5. Framing the digital transformation journey for sustainability from the lenses of integrated skills and competencies for the future work / Joseph O. Onyango -- Chapter 6. Role of social networking technologies in developing public services supply chain during covid-19 / Kali charan Sabat and Som Sekhar Bhattacharyya -- Chapter 7. Adopting technology for sustainable development: Reflections on innovative ecosystem / Jasmandeep Kaur, Kirandeep Kaur, and Ramanjeet Singh -- Chapter 8. Exploring the relationship between digital initiatives, dynamic capabilities, and market performance: A conceptual framework / Lan Phuong Ho Dang -- Chapter 9. Reverse logistics: Rebuilding smart and sustainable transformation based on industry 4.0 / Leena Wanganoo and Rajesh Tripathi -- Chapter 10. Reflections on sustainable development, sustainability, and business practice: Lessons from measurement, scalability, and bias in ai / Luisa F. Melo -- Chapter 11. Digital healthcare and patient transformation: Review research and future agenda / Nimesh P. Bhojak, Suresh N. patel, and Mohammadali K. Momin -- Chapter 12. A comparative framework analysis of the strategies, challenges, and opportunities for sustainable smart cities / Oluwagbemiga Paul Agboola and Meryem Muzeyyen Findikgil -- Chapter 13. Leveraging blockchain technology in adopting digital tokenisation of green bonds
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Sustainable development; Business & Economics -- Development -- Sustainable Development; Sustainability